Elucidation and quantification health-promoting phenolic compounds, antioxidant properties and sugar levels of ultrasound assisted extraction, aroma compositions and amino acids profiles of macroalgae, Laurencia papillosa - Gulden Goksen (Ultrasonics Sonochemistry, 2023)
Currently, sustainability is one of the most critical issues confronting society today. The growing of macroalgae in ocean farms appears more sustainable than agriculture on land due to it does not require any fresh water, chemical fertiliser, or soil. Macroalgae have been shown to be a sustainable marine source of amino acids, novel bioactive phenolic and aroma compounds that can be exploitation in food, cosmetic, nutraceuticals, pharmacological applications. Despite starting the huge cultivation of macroalgae in world, bioactive compounds in the edible macroalgae have not been well characterized. Ultrasound assisted extraction (UAE) and conventional extraction (CE) techniques were compared and red macroalgae, L. papillosa extracts were characterized. The highest amount of amino acid was glutamic acid (GLU) and composed of 35% was essential amino acids. UAE at 10% amplitude for 15 min showed significantly highest (p < 0.05) phenolic (212.03±3.03 mg gallic acid equivalent/100 g) as well as antioxidant activity determined by DPPH (105.69±3.02 µmol Trolox/100 g), ABTS (238.69±2.23 µmol Trolox/100 g) radical assay and FRAP value (72.47±3.13 µmol Trolox/100 g) when in comparison with CE. Furthermore, bioactive compounds in extracts were indicated as phlorotannins, flavonoids, phenolic acids and other polyphenols using liquid chromatography coupled to diode array detection and electrospray ionisation tandem mass spectrometry (LC-DAD-ESI-MS/MS). This result confirmed higher antioxidant capacity detected with the UAE. A total of 46 volatile organic compounds were identified and quantified by GC-FID/MS with HS-SPME system. This study emerges as first report to novel extraction method used and deeply characterization of L papillosa. The results seem that significant potential application in the functional food, active packaging and nutraceuticals industry.